Morphological and genomic characteristics of two novel actinomycetes, Ornithinimicrobium sufpigmenti sp. nov. and Ornithinimicrobium faecis sp. nov. isolated from bat faeces (Rousettus leschenaultia and Taphozous perforates) - Huang, Yuyuan; Zhang, Suping; Tao, Yuanmeihui; Yang, Jing; Lu, Shan; Jin, Dong; Pu, Ji; Luo, Wenbo; Zheng, Han; Liu, Liyun; Jiang, Jia-fu; Xu, Jianguo (Frontiers in Cellular and Infection Microbiology, 2023)
Four Gram-staining-positive, aerobic, non-motile, circle-shaped bacteria were isolated from the faeces of bats collected from Guangxi autonomous region (E106°49′20″, N22°20′54″) and Yunnan province (E102°04′39″, N25°09′10″) of South China. Strains HY006T and HY008 shared highly 16S rRNA gene sequence similarity to those of Ornithinimicrobium pratense W204T (99.3%) and O. flavum CPCC 203535T (97.3%), while the strains HY1745 and HY1793T were closest to the type strains O. ciconiae H23M54T (98.7%), O. cavernae CFH 30183T (98.3%), and O. murale 01-Gi-040T (98.1%). Furthermore, when compared to the other members of the genus Ornithinimicrobium, the digital DNA-DNA hybridization and average nucleotide identity values of the four novel strains were within the ranges of 19.6–33.7% and 70.6–87.4%, respectively, both of which were below the respective recommended cutoff values of 70.0% and 95–96%. Significantly, strain HY006T was resistant to chloramphenicol and linezolid whereas strain HY173T was resistant to erythromycin, clindamycin (intermediately), and levofloxacin (intermediately). The main cellular fatty acids (>20.0%) of our isolates were iso-C15:0 and iso-C16:0. Strains HY006T and HY1793T contained ornithine as the diagnostic diamino acid, also along with the alanine, glycine and glutamic acid in their cell wall. Based on phylogenetic, chemotaxonomic and phenotypic analyses, these four strains could be classified as two novel species of the genus Ornithinimicrobium, for which the names Ornithinimicrobium sufpigmenti sp. nov. and Ornithinimicrobium faecis sp. nov. are proposed. The type strains are HY006T (=CGMCC 1.16565T =JCM 33397T) and HY1793T (=CGMCC 1.19143T =JCM 34881T), respectively.